2000
DOI: 10.1038/sj.jhh.1001117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of hypertension in the elderly: results from a population survey

Abstract: Prevalence, awareness, treatment and control of hypertension were assessed in 1032 (90%) of 1147 elderly (у65 years) inhabitants of three Italian villages. Blood pressure (BP) was measured at home on two separate occasions following a standardised protocol. Persons taking antihypertensive drugs or with BP values у140/90 mm Hg were considered as affected by hypertension. Prevalence of hypertension was 64.8%, with higher rates in women than men, and in those aged 75-84 than in those aged 65-74. Diabetes, strokes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 24 publications
7
29
6
Order By: Relevance
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…36 The prevalence of hypertension and its awareness, treatment and control in studies conducted exclusively among the elderly and using our criteria for defining hypertension is given in Table 5. 14,15,17,[19][20][21][22][23][24][25][26][27] Although most of these studies reported a lower prevalence of hypertension 17,20,[22][23][24][25]27 than what we observed (73.9%), some Hypertension among elderly Singaporeans R Malhotra et al reported a similar prevalence 14,19,21,23,26 or, in one study, 15 an even higher prevalence. Other than differences in the BP measurement instrument (manual or electronic) and number of readings (two or three) used for defining SBP and DBP, the variation could also reflect differences in demographic (for example, age, gender, ethnicity) and lifestyle (for example, diet, physical activity) profiles and in economic development across countries (prevalence is usually higher in more developed economies 38 ).…”
Section: Discussioncontrasting
confidence: 52%
“…A variety of socio-demographic and health variables, evaluated as potential correlates with hypertension and/or awareness, treatment and control of hypertension in previous studies, 6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27]32 were evaluated as correlates in the present analysis.…”
Section: Correlatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological surveys in the USA and in Europe have shown prevalence rates varying from 53-72.3%. [7][8][9][10][11][12] Our study has potential limitations. The trend demonstrated in our study for higher prevalence among men compared with women was observed in surveys among younger study populations.…”
mentioning
confidence: 99%